Caffeine Supplementation in Semen Extender Protects Buffalo Spermatozoa from Cryodamage - Chavda, Bhakti P.; Vala, Karsan B.; Solanki, Gajendra B.; Prajapati, Sunny G.; Singh, Vivek Kumar (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
Caffeine is widely known for its phosphodiesterase enzymes inhibiting, and its powerful reactive oxygen species scavenging property. This study aimed to evaluate the effect of caffeine supplementation @ 0 mM, 1 mM, 3 mM and 5 mM in AndroMed® extender on cryopreservation of Jaffarabadi buffalo semen. Twenty-four semen ejaculates (6/bull) with >70% initial sperm motility were obtained from four mature Jaffarabadi bulls using AV. The ejaculates were split-diluted in an egg-yolk-free AndroMed® extender supplemented with different concentrations of caffeine and were cryopreserved using a standard protocol. The semen samples were evaluated for sperm quality parameters as well as oxidative stress parameters, viz., lipid peroxidation, and Glutathione-S-transferase (GST) enzyme activity in seminal plasma at pre-freeze (after equilibration) and post-thaw stage. The levels of caffeine had a significant effect on all these parameters, except sperm abnormalities, at both pre-freeze and post-thaw stages. Supplementation of caffeine in semen extender at 1 mM and 3 mM concentration showed a significant (p<0.05) increase in post-thawed sperm motility (62.04 ± 0.84, 61.25 ± 1.01%), viability (64.21 ± 0.88, 64.25 ± 0.84%), acrosome integrity (58.08 ± 1.08, 57.30 ± 0.93%) and plasma membrane integrity (52.75 ± 0.89, 52.71 ± 0.74%) and a significant (p<0.05) decrease in oxidative damage as evident by lower lipid peroxidation (MDA 7.62 ± 0.41, 7.80 ± 0.70 μM) and GST enzyme activity (31.15 ± 1.36, 29.54 ± 0.54 nmol CDNB/mL/min) as compared to control and 5 mM caffeine. The study concludes that the post-thaw quality of frozen semen of Jaffarabadi buffalo bulls improves significantly with decreased oxidative stress if the AndroMed® extender is supplemented with 1 and 3 mM concentration of caffeine over control.